2015
DOI: 10.1186/s40494-015-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman spectral identification of manganese oxides black pigments in an archaeological context in Northern Chile

Abstract: The micro-Raman spectroscopy was used to identify manganese oxides, pyrolusite, manganite and cryptomelane in archaeological sites in northern Atacama Desert, Chile. The present micro-Raman data allow us to compare and expand the origins of raw materials used by archaic groups of the Atacama Desert. In the Andean highlands, pyrolusite and manganite were identified while in the coastal lowlands manganite and cryptomelane were found. The present results complement the data obtained from the lithic materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
2
26
0
4
Order By: Relevance
“…The XRD and ICP‐OES elemental profiles of the Chinchorro samples are consistent with those reported by Sepúlveda, Laval, et al (), Sepúlveda, Valenzuela, et al (), and Sepúlveda et al (, ) and XRD results from the Huaylas samples are also similar to those reported by Hewett & Olivares () and Ossa (). The Chinchorro samples are dominated by cryptomelane and lesser amounts of rhodochrosite, which suggests the manganese was not derived from soil nodules, marine nodules or diagenetic beds.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The XRD and ICP‐OES elemental profiles of the Chinchorro samples are consistent with those reported by Sepúlveda, Laval, et al (), Sepúlveda, Valenzuela, et al (), and Sepúlveda et al (, ) and XRD results from the Huaylas samples are also similar to those reported by Hewett & Olivares () and Ossa (). The Chinchorro samples are dominated by cryptomelane and lesser amounts of rhodochrosite, which suggests the manganese was not derived from soil nodules, marine nodules or diagenetic beds.…”
Section: Discussionsupporting
confidence: 90%
“…The compound paste used to make Chinchorro masks and also hold the wig in place have higher concentrations of MnO and lower concentrations of SiO 2 and Al 2 O 3 than the Lauca/Upper Huaylas samples. Although the exact methodology used by the Chinchorro has yet to be established, based on how manganese pigments were created in other historical cultures, it is likely the material was finely ground, separated and mixed with a binder so it would adhere to the masks and bodies (Barham, ; Chalmin et al, ; d’Errico, Salomon, Vignaud, & Stringer, ; Sepúlveda, Laval, et al, ; Sepúlveda, Valenzuela, et al, ; Sepúlveda et al, , ; Vandiver, ). This process of high‐grading the manganese fraction of the rock could explain the ICP‐OES variations observed between these two sample populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The black colour is because of the occurrence of a variety of manganese oxides (Mn x O y ) in the pigment. Exact identification of the specific variety is difficult . Manganese oxides and oxyhydroxides show high thermal opacity and absorption.…”
Section: Resultsmentioning
confidence: 99%
“…No âmbito da Ciência do Patrimônio, a técnica vem sendo aplicada em estudos variados. No caso de pinturas rupestres diversas publicações podem ser encontradas na literatura (DARCHUK et al, 2010;DE FARIA e LOPES, 2011;DE FARIA e MENEZES, 2011;ROUSAKI et al, 2015;SEPULVEDA et al, 2015;MOYA et al, 2016;TASCON et al, 2016;GHECO et al, 2017;ROUSAKI et al, 2017;TRONCOSO et al, 2017;MORILLAS et al, 2018) sendo que o objetivo mais frequente é a identificação de pigmentos usados na produção das pinturas (DARCHUK et al, 2010;ROUSAKI et al, 2015;TASCON et al, 2016;GHECO et al, 2017;ROUSAKI et al, 2017) com a perspectiva de ampliar o conhecimento sobre práticas e técnicas dominadas por diferentes culturas ou, ainda, compreender melhor os processos associados à deterioração dos pictogramas (DE FARIA e MENEZES, 2011;FARIAS FILHO et al, 2017;MORILLAS et al, 2018). Tais análises foram usualmente feitas em amostras coletadas das pinturas seguindo procedimentos aprovados pelos órgãos de proteção ao patrimônio cultural, mas há uma publicação na qual os espectros foram obtidos in situ com o uso de instrumento portátil com duas radiações de excitação (532 nm and 785 nm) (ROUSAKI et al, 2017); nesse artigo são destacadas algumas das dificuldades encontradas no uso em campo desse tipo de instrumento.…”
Section: Aplicações Em Estudos De Bens Culturais -América Do Sulunclassified